问题标题:
【为什么1的三次方+2的三次方+3的三次方+······+n的三次方=[n×(n+1)/2]的平】
问题描述:
为什么1的三次方+2的三次方+3的三次方+······+n的三次方=[n×(n+1)/2]的平
潘锐回答:
(1+1)^4=1^4+4*1^3+6*1^2+4*1^1+1
(2+1)^4=2^4+4*2^3+6*2^2+4*2^1+1
(3+1)^4=3^4+4*3^3+6*3^2+4*3^1+1
……
(n+1)^4=n^4+4*n^3+6*n^2+4*n^1+1
相加
(1+1)^4+(2+1)^4+(3+1)^4+……+(n+1)^4=
1^4+4*1^3+6*1^2+4*1^1+1+
2^4+4*2^3+6*2^2+4*2^1+1+
3^4+4*3^3+6*3^2+4*3^1+1+
……+
n^4+4*n^3+6*n^2+4*n^1+1
消去2到n的4次项
(n+1)^4=1^4+
4*1^3+6*1^2+4*1^1+1+
4*2^3+6*2^2+4*2^1+1+
4*3^3+6*3^2+4*3^1+1+
……+
4*n^3+6*n^2+4*n^1+1
设
A=1^3+2^3+3^3+……+n^3
B=1^2+2^2+3^2+……+n^2
C=1+2+3+……+n=n(1+n)/2
代入ABC
(n+1)^4=1^4+4A+6B+4C+n
A=((n+1)^4-6B-4C-n-1)/4=((n+1)^4-6B-2n(1+n)-n-1)/4
计算B
(1+1)^3=1^3+3*1^2+3*1+1
(2+1)^3=2^3+3*2^2+3*2+1
(3+1)^3=3^3+3*3^2+3*3+1
……
(n+1)^3=n^3+3*n^2+3*n+1
(1+1)^3+(2+1)^3+(3+1)^3+……+(n+1)^3=
1^3+3*1^2+3*1+1+
2^3+3*2^2+3*2+1+
3^3+3*3^2+3*3+1+
……+
n^3+3*n^2+3*n+1
(n+1)^3=1^3
3*1^2+3*1+1+
3*2^2+3*2+1+
3*3^2+3*3+1+
……+
3*n^2+3*n+1
(n+1)^3=1+3B+3C+n
B=((n+1)^3-3C-n-1)/3=((n+1)^3-3n(1+n)/2-n-1)/3=n(n+1)(2n+1)/6
A=((n+1)^4-6B-2n(1+n)-n-1)/4
=((n+1)^4-n(n+1)(2n+1)+2n(1+n)-n-1)/4
化简
A=(n(n+1)/2)^2
点击显示
数学推荐
热门数学推荐